Evaluation of a Soluble Fibrin Assay in Patients with Suspected Pulmonary Embolism - Ginsberg, Jeffrey S; Siragusa, Sergio; Douketis, James; Johnston, Marilyn; Moffat, Karen; Donovan, Dianne; McGinnis, Joanne; Brill-Edwards, Patrick; Panju, Akbar; Patel, Ameen; Weitz, Jeffrey I (Thrombosis and Haemostasis, 1996)
In order to determine the clinical utility of an enzyme immunoassay (EIA) for soluble fibrin in patients with suspected pulmonary embolism (PE), 195 unselected patients with suspected PE underwent blood sampling for measurement of plasma levels of soluble fibrin, and objective testing for PE. A soluble fibrin result of ≤ 0.75 Μg/ml showed a sensitivity of 100% for PE and a specificity of 12.8%, whereas a soluble fibrin result of ≤ 1.35 Μg/ml showed a sensitivity of 90.3% and a specificity of 49.4% for PE. The soluble fibrin assay has potential clinical utility in excluding PE.